A modified two-stage isolated bidirectional buck-DAB converter with a full-load ZVS range - Li, Jinliang; Wan, Dai; Lu, Zhengmei; Xu, Guo (Frontiers in Energy Research, 2024)
A modified two-stage Buck-DAB converter (MBDAB) is proposed to improve the performance of the traditional two-stage Buck-DAB (TSBDAB). In the MBDAB converter, the DAB can work with fixed voltage gain and voltage matched condition under a wide input voltage range. The voltage gain of the converter is adjusted through the added front-end stage which is similar to a buck converter. Compared with the TSBDAB converter, only part of the transmitted power flows through the front-end stage, so the loss of the Buck stage and the burden of ZVS can be reduced. Detailed analysis of the working principle, partial power characteristics, and the full load range ZVS design are presented. To verify the effectiveness of the proposed MBDAB, experimental results are obtained from a prototype with a rated power of 1kW.